Correlates of successful transition in young adults with sickle cell disease. Issue 12 (20th August 2019) - Darbari, Isha; Jacobs, Emily; Gordon, Olivia; Weiss, Diane; Winship, Kim; Casella, James F.; Strouse, John J.; Takemoto, Clifford M.
Abstract: The transition period from pediatric care to adult care for patients with sickle cell disease (SCD) is associated with increased mortality and morbidity. Identification of risk factors for unsuccessful transition may aid in developing strategies to improve the transition process and health outcomes in this population. We examined factors associated with unsuccessful transition from pediatric to adult care for patients with SCD at the Johns Hopkins Hospital. We found that public insurance and increased hospitalization rates were associated with poor transition to adult care. The findings provide possible areas of intervention.